1984
DOI: 10.1073/pnas.81.14.4544
|View full text |Cite
|
Sign up to set email alerts
|

Genomes of evolutionarily divergent members of the human T-cell leukemia virus family (HTLV-I and HTLV-II) are highly conserved, especially in pX.

Abstract: Human T-cell leukemia virus (HTLV) is a family of related human T-lymphotropic retroviruses closely linked with certain human T-cell malignancies and associated with many cases of acquired immunodeficiency syndrome (AIDS). We isolated and molecularly cloned HTLV from patients with both types of clinical disorders and found by restriction endonuclease mapping and core and envelope protein analysis that at least two evolutionarily divergent viral subgroups exist, HTLV-I and HTLV-II. Previous studies have failed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…The nucleotide sequence homology of the two viruses has been investigated. Studies carried out with Southern blotting and heteroduplex mapping at different melting points showed that both viruses had strongly conserved nucleotide sequences in the pX region and less-conserved regions in the LTR, gag, pol and env regions although they are still substantially homologous (Shaw et al, 1984). These data show that both viruses are evolutionarily divergent members of HTLV and suggest that thepX region of HTLV may play an important role in the transformation of cells.…”
Section: Htl Via Tl V Strainsmentioning
confidence: 82%
“…The nucleotide sequence homology of the two viruses has been investigated. Studies carried out with Southern blotting and heteroduplex mapping at different melting points showed that both viruses had strongly conserved nucleotide sequences in the pX region and less-conserved regions in the LTR, gag, pol and env regions although they are still substantially homologous (Shaw et al, 1984). These data show that both viruses are evolutionarily divergent members of HTLV and suggest that thepX region of HTLV may play an important role in the transformation of cells.…”
Section: Htl Via Tl V Strainsmentioning
confidence: 82%
“…The virus is also of interest because it can serve as an experimental model for a family of lymphotropic retroviruses which contains human T cell leukaemia viruses HTLV-I and HTLV-II (Oroszlan et al, 1982;Shaw et al, 1984). The susceptibility of cells from various animal species to BLV infection in vitro is quite broad (Graves & Ferrer, 1976;Altaner et al, 1987a, b).…”
mentioning
confidence: 99%
“…Interestingly, analogous gene regions encoding the accessory proteins, especially the pX ORF I-encoded p12 I , are highly conserved in the closely related virus HTLV-2 and the nonhuman primate counterpart of HTLV-1, simian T-cell lymphotropic virus type 1 (23,110,115). Further illustration of the conserved nature of these gene regions comes from studies of another member of the deltaretroviruses, bovine leukemia virus (BLV).…”
Section: Htlv-1 Accessory Proteins Expressed From Px Gene Regionmentioning
confidence: 99%